Earth's cycles - Dakers, Diane (Dakers, Diane. Earth's cycles in action., 2015)
"Explains the patterns and cycles created on Earth by the influence of the Sun and the Moon, as well as by the Earth's magnetic poles and the planet's rotation on an axis"--Provided by publisher.